Septal hematoma due to stent implementation in the septal course of the left anterior descending artery - Khameneh-Bagheri, Ramin (ARYA Atheroscler, 2017)
BACKGROUND: The interventricular septal hematoma (IVSH) is a rare and potentially lethal finding. There are variously reported etiologies including instrumental damages during cardiac interventions. Although there are not enough studies available, conservative management is considered as a preferable approach in stable patients. CASE REPORT: A 45-year man smoker with the previous history of percutaneous coronary intervention (PCI), admitted with unstable angina in present visit. Coronary angiography showed significant in-stent restenosis (ISR) of the left anterior descending (LAD) artery stent. During our intervention for treatment of the ISR, the wire movement caused a diffuse dissection without any runoff, in the distal portion of the LAD. Therefore two stents were deployed in the dissected segment with a short overlapping segment. Unfortunately, the overlapping segment of these stents was located in the myocardial bridge segment. Therefore the contraction of the interventricular septum (IVS) caused a scissor-like movement of the stents, and they ruptured the LAD into the septum. Therefore, the contrast agent was accumulated in the IVS. Immediately, a graft stent was deployed in the overlapping segment of stents and perforation became sealed. In echocardiography, the IVS diameter increased to 30 mm. Since the patient was hemodynamically and electrically stable, he underwent conservative approach and after two months the septum returned to the normal size. CONCLUSION: During PCI on the LAD artery, the implantation of stents in the septal course with a short overlapping segment can result in coronary perforation, and therefore IVS hematoma by the scissor effect. Septal hematoma may cause life-threatening arrhythmias or ventricular septal rupture, but if it is asymptomatic or uncomplicated. Conservative management is the best strategy.